THE CONTRIBUTIONS OF HEIDEGGARIAN PHILOSPHY IN RESEARCH ABOUT CARE IN NURSING - Marianne Rocha Duarte; Silvana Santiago da Rocha (Universidade Federal do Paraná, 2011)
This article aims to reflect on the contributions of Heideggerian phenomenology to the comprehension of dimensions of care in Nursing. Although care has been the focus of various studies in an effort to understand its significance, one can see a research gap in relation to the existential dimensions of the human being. In this sense, research on nursing care using Martin Heidegger's philosophy would make it possible for health professionals and future health professionals to reflect on their practice, appearing more clearly to themselves and the world around them, and becoming more attentive and reflexive health professionals, able to care in a more authentic manner at the same time as Nursing shows the meaning of its care.